1992
DOI: 10.1111/j.1471-4159.1992.tb11025.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mechanisms for Inhibition of Excitatory Amino Acid Receptors Coupled to Phosphoinositide Hydrolysis

Abstract: Excitatory amino acid (EAA) analogues activate receptors that are coupled to the increased hydrolysis of phosphoinositides (PIs). In these studies, hippocampal slices were prepared from neonatal rats (6-11 days old) to characterize the effects of EAA analogues on these receptors. The concentrations of ibotenate and trans-(+/-)-1-amino-1,3-cyclopentanedicarboxylate (trans-ACPD) required to evoke half-maximal stimulation (EC50 values) were 28 and 51 microM, respectively. Although the data for stimulation of PI h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 39 publications
4
33
0
Order By: Relevance
“…47,48 Moreover, HDX could inhibit matrix metalloproteinases and AAT activities, in addition to reversing the increased AAT levels in plasma as demonstrated by a few rat experiments. [49][50][51] Furthermore, HDX could inhibit AAT activities and the generation of endogenous SO 2 in both pulmonary tissues and myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 Moreover, HDX could inhibit matrix metalloproteinases and AAT activities, in addition to reversing the increased AAT levels in plasma as demonstrated by a few rat experiments. [49][50][51] Furthermore, HDX could inhibit AAT activities and the generation of endogenous SO 2 in both pulmonary tissues and myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Although AP3 has been shown to inhibit 3[H]-glutamate uptake into synaptosomes (Littman et al, 1992), it is not clear whether AP3 is a substrate for transport. We addressed this issue using whole-cell patch clamp recordings in microcultures of hippocampal astrocytes (Mennerick and Zorumski, 1994).…”
Section: L-ap3 Exhibits Features Of a Glutamate "Ransport Substratementioning
confidence: 99%
“…Previous studies indicate that AF' 3 inhibits glutamate transport (Littman et al, 1992). To determine whether effects on glutamate transporters contribute t o AP3-induced damage, we examined the effects of the glutamate transport inhibitors D,L-threo-3-hydroxyaspartate (THA), pyrrolidine dicarboxylic acid (PDC), D,L-aminoadipic acid (AAA), and dihydrokainate (DHK) ( Table 1).…”
Section: Glutamate Transport Inhibitors Mimic Ap3-induced Glial Swellingmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that L-trans-PDC is transportable also implies that, when it is applied extracellularly, it may also produce carrier-mediated efflux of glutamate (heteroexchange) (Waldmeier et al 1993;Griffiths et al 1994). Some studies have suggested that L-trans-PDC may have agonistic actions on metabotropic receptors (mGluR) (Littman et al 1992;Miller et al 1994). However, there is some controversy on the origin of these effects, because they could actually be secondary to heteroexchange (Thomsen et al 1994;Desai et al 1995).…”
Section: Advantages and Limitations Of L-trans-pdcmentioning
confidence: 99%